PENGARUH RETURN ON EQUITY, DIVIDEND PAYOUT RATIO, PRICE TO BOOK VALUE DAN EARNING PER SHARE TERHADAP RETURN SAHAM (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2015) - Ariani, Mufty, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2017)
The purpose of this study was to determine the effect of capital return on equity, dividend payout ratio, price to book value, and earning per share on stock return. Population of this research are manufacturing companies listed in Indonesian Stock Exchange 2013-2015 period. Total sample on this research are 102 manufacturing companies, samples were detremined with purposive sampling method. Analysizes techniqueus using multiple regression analysize. The result of the study shows that Dividend Payout Ratio and Earning Per Share have effect (significant) on stock return, while Return On Equity dan Price to Book Value don't have effect (not significant) on stock return.